The psychopathological roots of affective dependence: The origin and clinical evolution of the toxic bond - Giulio Perrotta (Annals of Psychiatry and Treatment - Peertechz Publications, 2022)
Background and aims: Starting from the concept of "affective addiction", then reworked and critiqued according to a clinical key, it was hypothesized that it is not a behavioral addiction, as erroneously determined by modern psychiatry, but is a symptom of a well-identified personality disorder. The purpose of this research is to test the correctness of this hypothesis.  Materials and methods: Clinical interview, based on narrative-anamnestic and documentary evidence and the basis of the Perrotta Human Emotions Model (PHEM) concerning their emotional and perceptual-reactive experience, and administration of the battery of psychometric tests published in international scientific journals by the author of this work: 1) Perrotta Integrative Clinical Interviews (PICI-2), to investigate functional and dysfunctional personality traits; 2) Perrotta Individual Sexual Matrix Questionnaire (PSM-Q), to investigate the individual sexual matrix; 3) Perrotta Affective Dependence Questionnaire (PAD-Q), to investigate the profiles of affective and relational dependence; 4) Perrotta Human Defense Mechanisms Questionnaire (PDM-Q), to investigate the defense mechanisms of the Ego.  Results: In a population sample of 206 subjects (103 m/f couples, in a stable relationship for at least 1 year and heterosexual), it was found that the totality exhibited at least 5 dysfunctional personality traits of the borderline, dependent, and masochistic types, with secondary traits of the neurotic, narcissistic covert, psychotic and histrionic types. Almost the totality of the sample also showed marked dysfunctionality of a sexual nature and activation of defense mechanisms typical of psychopathological processes.  Conclusions: The data obtained confirmed the study hypothesis, and it is, therefore, plausible to think that affective addiction is not a behavioral addiction but a manifested symptom of a broader framework of personality disorder and that it is established in subjects with the same dysfunctional personality traits. Such subjects, in close relational contact, hyperactivate themselves, according to a logic of pathological determinism. The maintenance of hyperactivation then facilitates the decompensation of the subject's psychopathological picture, reinforcing dysfunctionality and feeding the pathological circle that keeps one's personality structure alive, in a continuous feeding determined by the similar or same-natured traits present in the partner. This also explains why, once affective dependence is established, it is so complicated to succeed in breaking the chain of events that keeps the dysfunctional relationship alive, since overactivation prevents a correct, conscious, and rational assessment of the factors at play in relationships between elements and people. To summarize: the more the hyperactivation persists, the more it reinforces the psychopathological decompensation that keeps alive both the toxic relationship and the bond between the two individuals who, while tending toward destruction or self-destruction, fail to break the affective, sentimental, and sexual bond, maintaining over time an increasingly toxic dysfunctional attachment.